2,2 '- Nonane-1,9-diylbis(nitrilomethylidyne) Diphenol - Abdullah, N.; Lo, K.M.; Tajuddin, Hairul Anuar; Tee, J.T.; Ng, S.W. (International Union of Crystallography, 2008)
In the title Schiff base compound, C(23)H(30)N(2)O(2), the complete molecule is generated by crystallographic twofold symmetry, with one C atom lying on the rotation axis. The nonane chain adopts a linear conformation and the hydroxy group forms an intramolecular O-H center dot center dot center dot N hydrogen bond to the imine group.